Tartary buckwheat malt as ingredient of gluten-free cookies. (March 2018) - Molinari, Romina; Costantini, Lara; Timperio, Anna Maria; Lelli, Veronica; Bonafaccia, Francesco; Bonafaccia, Giovanni; Merendino, Nicolò
Abstract: The impact of malting on the profile of the phenolic compounds and the antioxidant properties of tartary buckwheat ( Fagopyrum tataricum L. Gaertn.) was investigated. A considerable increase in total phenolic compounds and higher antioxidant activity were observed after 88 h of germination. The highest relative increases in phenolic compounds were observed for quercetin, orientin, and vitexin, which are consequently major inducible phenolic compounds during malting. Only a minor relative increase was observed for the most abundant phenolic compound, rutin. Formulations of gluten-free cookies based on rice flour and buckwheat malt or flour in ratios 70:30, have been produced. In the raw material and cookies the proximate composition, starch, resistant starch, total polyphenols, profile of polyphenols, antioxidant activity and expected glycemic index were determined. Gluten-free cookies made with rice flour and buckwheat malt exhibited significantly higher total phenolic and quercetin contents. Comparing to control cookies higher antioxidant activity and lower glycemic index (p < 0.05) was found. Highlights: Composition of phenolics in tartary buckwheat malt was studied. Major inducible phenolics were quercetin orientin, vitexin, and rutin. Antioxidant capacity of buckwheat seeds was positively affected by malting. Tartary Malt Cookies (TMC) 70:30 rice flour and buckwheat malt were produced. TMC have a higher phenols content, antioxidant capacity, and lower glycemic index.